2016
DOI: 10.1161/circheartfailure.116.003291
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Reduces Cardiac Contractility via EP3 Receptor

Abstract: Background Prostaglandin E2 (PGE2) EP receptors EP3 and EP4 signal via decreased and increased cAMP production, respectively. Previously we reported that cardiomyocyte-specific EP4 KO mice develop dilated cardiomyopathy with reduced ejection fraction. We thus hypothesized that PGE2 increases contractility via EP4 but decreases contractility via EP3. Methods and Results The effects of PGE2 and the EP1/EP3 agonist sulprostone on contractility were examined in the mouse langendorff preparation and in adult mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…Since we also recently reported that PGE 2 via its EP3 receptor reduced contractility of the heart via mechanism(s) that appeared to involve decreased phospholamban phosphorylation; we examined phosphorylation of phospholamban in these studies. Sham-operated mice who received AAV9-EP4 exhibited a significant increase in phosphorylated phospholamban, consistent with our in vitro data using the EP4 agonist in isolated cardiomyocytes [4]. A similar trend was observed in animals with MI, although the data did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Since we also recently reported that PGE 2 via its EP3 receptor reduced contractility of the heart via mechanism(s) that appeared to involve decreased phospholamban phosphorylation; we examined phosphorylation of phospholamban in these studies. Sham-operated mice who received AAV9-EP4 exhibited a significant increase in phosphorylated phospholamban, consistent with our in vitro data using the EP4 agonist in isolated cardiomyocytes [4]. A similar trend was observed in animals with MI, although the data did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…These effects appeared to involve changes in the phosphorylation of phospholamban. Moreover, we also reported that after MI, expression of the EP3 receptor subtype in the left ventricle was increased to a greater extent than EP4 [4]. We therefore hypothesized that overexpression of EP4 in the heart would improve cardiac function after MI.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Oxylipins have many biological functions, and several effects of free oxylipins on the heart in health and disease have been shown (3,4) . For example, ARA-derived PGE 2 modulates cardiac contractility depending on which receptor it activates (5) , 19-hydroxyeicosatetraenoic acid (19-HETE) reduces cardiomyocyte hypertrophy (6) , 20-HETE and epoxy-eicosatrienoic acids (EpETrE) induce cardiac hypertrophy (7) , EpETrE prevent lipopolysaccharide-induced cardiac dysfunction (8) and 5-, 12and 15-HETE induce cellular hypertrophy in human ventricular cardiomyocytes (9) . Oxylipins derived from other PUFA also have effects on the heart, such as EPA-derived 18-hydroxy-eicosapentaenoic acid , which is anti-inflammatory in cardiac fibroblasts (10) , and DHA-derived 13,14-epoxydocosapentaenoic acid (13,14-EpDPE), which potently dilates porcine coronary microvessels (11) .…”
mentioning
confidence: 99%